PENINGKATAN PEMAHAMAN DAN KETRAMPILAN CALON GURU JEMAAT HKBP TENTANG PODA TOHANAN - Simanungkalit, Manaek (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThis Community Service Program (PKM) is carried out to improve the understanding and skills of prospective Congregation Teachers HKBP at STGH HKBP Sipoholon in applying Poda Tohonan as the primary foundation of their ministry duties. The church, as a community of faith, bears the responsibility to nurture its members, particularly through the role of Congregation Teachers, who are expected to demonstrate mastery of pedagogical, theological, and spiritual role-modeling. Preliminary findings reveal that aspiring Congregation Teachers are still encountering a range of obstacles, particularly the lack of comprehensive theological insight, varying understandings of their service duties, and ongoing issues related to managing time, maintaining motivation, and sustaining discipline. The activity strategy encompasses material delivery, interactive discussions, mentoring sessions, and structured reflection activities. The evaluation is conducted through written tests and practical observations. The activities indicate an improvement in participants’ knowledge of Poda Tohonan from 40% to 85%. The participants also demonstrate progress in leading worship, guiding congregants, and applying pedagogical principles. The approach, based on lectures, discussions, mentoring, and reflection, has proven effective in helping participants integrate theory with practice. Keywords: Understanding and Skills, Congregation Teachers, Poda Tohonan ABSTRAKKegiatan Pengabdian kepada Masyarakat (PKM) ini dilaksanakan untuk meningkatkan pemahaman dan keterampilan calon Guru Jemaat HKBP di STGH HKBP Sipoholon dalam menerapkan Poda Tohonan sebagai landasan utama tugas pelayanan. Gereja sebagai komunitas iman memiliki tanggung jawab untuk membina jemaat, termasuk melalui peran Guru Jemaat yang dituntut menguasai aspek pedagogis, teologis, dan keteladanan rohani. Observasi awal menunjukkan masih adanya hambatan pada calon Guru Jemaat, seperti pemahaman teologis yang belum mendalam, interpretasi tugas yang beragam, serta tantangan dalam manajemen waktu, motivasi, dan disiplin. Strategi kegiatan mencakup penyampaian materi, diskusi interaktif, pendampingan, serta sesi refleksi. Evaluasi dilakukan dengan tes tertulis dan observasi praktik. Kegiatan menunjukkan peningkatan pengetahuanHH peserta terhadap Poda Tohonan dari 40% menjadi 85%. Peserta juga mengalami kemajuan dalam memimpin ibadah, membimbing jemaat, dan menerapkan prinsip pedagogis. Pendekatan berbasis ceramah, diskusi, mentoring, dan refleksi terbukti membantu peserta mengintegrasikan teori dengan praktik.Kata Kunci : Pemahaman dan Ketrampilan, Guru Huria, Poda Tohonan